2015
DOI: 10.1097/fpc.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

A family-specific linkage analysis of blood lipid response to fenofibrate in the Genetics of Lipid Lowering Drug and Diet Network

Abstract: Cost-effective identification of novel pharmacogenetic variants remains a pressing need in the field. Using data from the Genetics of Lipid Lowering Drugs and Diet Network, we identified genomic regions of relevance to fenofibrate response in a sample of 173 families. Our approach included a multipoint linkage scan, followed by selection of the families showing evidence of linkage. We identified a strong signal for changes in LDL-C on chromosome 7 (peak LOD score=4.76) in the full sample (n=821). The signal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In support of our findings are the reports of higher cholesterol levels in partially (55) or completely CD36-deficient individuals (9) and the higher LDL levels and abnormal cholesterol absorption of CD36-null mice (24,56). In addition, a recent linkage analysis of LDL particle response to fenofibrate treatment in GOLDN reported a peak encompassing the CD36 locus (57). Thus, the LDL associations we identified and their potential relationship to disease risk warrant further investigation.…”
Section: 11supporting
confidence: 78%
“…In support of our findings are the reports of higher cholesterol levels in partially (55) or completely CD36-deficient individuals (9) and the higher LDL levels and abnormal cholesterol absorption of CD36-null mice (24,56). In addition, a recent linkage analysis of LDL particle response to fenofibrate treatment in GOLDN reported a peak encompassing the CD36 locus (57). Thus, the LDL associations we identified and their potential relationship to disease risk warrant further investigation.…”
Section: 11supporting
confidence: 78%
“…Hidalgo et al [ 6 ] reported no linkage in their analysis of TG levels, using a different approach than the one we followed here. They relied primarily on MERLIN to both estimate IBD matrices and conduct linkage analyses.…”
Section: Discussionmentioning
confidence: 88%
“…Second, and possibly more important, it limited the number of loci that Hidalgo et al were able to use for IBD inference. Only 10 sets of approximately 3000 SNPs each were used to perform “linkage analyses in independent overlapping intervals of the genome” [ 6 ] from 729,490 SNPs that were available to them for analysis. By using IBDLD [ 7 ] we were able to leverage the information contained in more than 375,632 SNPs to derive our MIBD estimates at the 3561 loci that were used in our linkage analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations